Immune and pathophysiologic profiling of antenatal coronavirus disease 2019 in the GIFT cohort: A Singaporean case-control study - Gu, Yue; Low, Jia Ming; Tan, Jolene Su Yi; Ng, Melissa Shu Feng; Ng, Lisa F. P.; Shunmuganathan, Bhuvaneshwari; Gupta, Rashi; MacAry, Paul A.; Amin, Zubair; Lee, Le Ye; Lian, Derrick; Shek, Lynette Pei-Chi; et al. (Frontiers in Pediatrics, 2022)
COVID-19 can be severe in pregnant women, and have adverse consequences for the subsequent infant. We profiled the post-infectious immune responses in maternal and child blood as well as breast milk in terms of antibody and cytokine expression and performed histopathological studies on placentae obtained from mothers convalescent from antenatal COVID-19. 17 mother-child dyads (8 cases of antenatal COVID-19 and 9 healthy unrelated controls; 34 individuals in total) were recruited to the Gestational Immunity For Transfer (GIFT) study. Maternal and infant blood, and breast milk samples were collected over the first year of life. All samples were analyzed for IgG and IgA against whole SARS-CoV-2 spike protein, the spike receptor-binding domain (RBD), and previously reported immunodominant epitopes, as well as cytokine levels. The placentae were examined microscopically. The study is registered at clinicaltrials.gov under the identifier NCT04802278. We found high levels of virus-specific IgG in convalescent mothers and similarly elevated titers in newborn children. Thus, antenatal SARS-CoV-2 infection led to high plasma titres of virus-specific antibodies in infants postnatally. However, this waned within 3-6 months of life. Virus neutralisation by plasma was not uniformly achieved, and the presence of antibodies targeting known immunodominant epitopes did not assure neutralisation. Virus-specific IgA levels were variable among convalescent individuals’ sera and breast milk. Antibody transfer ratios and the decay of transplacentally transferred virus-specific antibodies in neonatal circulation resembled that for other pathogens. Convalescent mothers showed signs of chronic inflammation marked by persistently elevated IL17RA levels in their blood. Four placentae presented signs of acute inflammation, particularly in the subchorionic region, marked by neutrophil infiltration even though >50 days had elapsed between virus clearance and delivery. Administration of a single dose of BNT162b2 mRNA vaccine to mothers convalescent from antenatal COVID-19 increased virus-specific IgG and IgA titers in breast milk, highlighting the importance of receiving the vaccine even after natural infection with the added benefit of enhanced passive immunity.